Aplicación de técnicas básicas para mejorar la lecto-escritura en los estudiantes del tercer año del CECIBEB “Jhon F. kennedy” de la comunidad Mercedes Cadena del cantón Guamote, provincia de Chimborazo durante el año lectivo 2019-2020 - Tapia Benavides, Adela Lorena (2020)
At CECIBEB "JHON F. KENNEDY" of the Mercedes Cadena community in the canton guamote, deficits in reading and writing resulted in a low understanding of reading a text, as well as, when writing a text, the causes can be the strategies applied during the teaching process – learning, and little interest of students in reading, being the antecedent that gave rise to the realization of the present research, proposing as a goal, show that the application of basic techniques allows to improve the literacy in the students of the Third Year of BasicEducation. The research is Exploratory, Descriptive and Explanatory, based on the research of Campo and Documentary because it investigates and analyzes in the same place of the facts the application of basic techniques to improve literacy; in addition, because it relates directly to the actors immersed in the problem. The instruments used are the survey for obtaining data for the 7 students of the third basic year. The tab data is interpreted statistically and graphically and describes the before and after results have been applied basic techniques to develop literacy. It is concluded that strategies that contribute to the development of literacy using the Syllabic Method for Reading and Dictation to improve writing are required. Keywords: Basic Techniques, Literacy, Syllabic, Analytical, Oral, Copying and Dictation